Solar Irradiance Measurement Using Neuro Fuzzy Network (International Journal of Engineering and Computer Science, 2015)
Solar irradiance is a key parameter for MPPT in pv power plants.The operating point at which a pv array deliver its maximum power ,changes as a function of irradiance and temperature.If we sensed the both solar irradiance and temperature values we can easily compute maximum power point,moreover forcing pv array to operate at that point to increase effiency . Temperature sensing is easy, however, measuring solar irradiance is difficult because irradiance sensors are expensive and difficult to calibrate.To overcome those difficulties we go for measuring irradiance based on neuro fuzzy networks . The proposed sensor is implemented through a photovoltaic cell, a temperature sensor, and a low-cost microcontroller. The use of a microcontroller allows for easy calibration, updates, and enhancement by simply adding code libraries. Furthermore, it can be interfaced via standard communication means with other control devices, integrated into control schemes, and remote-controlled through its embedded web server.